Preparation method of dry-process thick pole piece

Through the dry thick electrode sheet preparation method, the problem of binder migration during traditional wet drying is solved, and uniform binder and conductive agent distribution is achieved, the transmission capacity of lithium ions and electrons is enhanced, and the electrochemical performance and energy density of lithium ion batteries are improved.

CN119627051APending Publication Date: 2025-03-14NINGBO GRAPHENE INNOVATION CENT CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411638152.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-16
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

During the traditional wet drying process, solvent volatility leads to binder migration, affecting the toughness and electrochemical properties of the electrodes. The processability and adhesion stability of the dry electrodes are insufficient, making it difficult to achieve a high-energy density lithium-ion battery.

Method used

The dry thick electrode sheet preparation method is adopted to achieve uniform distribution of binder and conductive agent through steps such as powder premixing, fibrosis, film formation, thinning and electrode diaphragm and current collector covering, thereby enhancing the transmission capacity of lithium ions and electrons.

Benefits of technology

A uniform microstructure design is achieved, the pore size distribution and conductive network of the electrode are improved, the transmission capacity of lithium ions and electrons is enhanced, the production cost and environmental pollution are reduced, and the electrochemical performance and energy density of lithium ion batteries are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119627051A_ABST
    Figure CN119627051A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of a dry-process thick pole piece, which specifically comprises the following steps: stirring and mixing active material powder, a binder and a conductive agent under the condition that the temperature is controlled to be less than or equal to 18 DEG C to obtain a premix; the obtained premix is subjected to rapid shearing, the temperature is increased to be smaller than or equal to 180 DEG C, and fiberized powder is obtained after the specified temperature is reached; carrying out one-time double-roller hot pressing on powder obtained after fibration to continuously form a film, continuously passing the formed film through double rollers, carrying out hot pressing and thinning, and then rolling to obtain a dry-method electrode film; the obtained dry-method electrode diaphragm and a current collector are subjected to continuous double-face covering through double-roller hot pressing, and a dry-method electrode thick electrode roll is obtained after rolling; the method has the advantages that effective transmission of lithium ions and electrons in the electrode is promoted, and the thick and compact electrode with uniform binder distribution is prepared.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of primary and secondary batteries and supercapacitors, and specifically to a method for preparing a dry thick electrode (the final electrode thickness reaches more than 500 μm). Background Art

[0002] The global demand for lithium-ion batteries is expected to increase sixfold (≈4,700 GWh) by 2030 compared to 2022 (≈700 GWh). Driven by the shift to sustainable development, the EU will ban internal combustion engine vehicles from 2035, and there will be a large demand for lithium-ion batteries for electric vehicles (EVs) in 2030. To meet the growing demand of the EV market, battery manufacturers are conducting research on high-productivity, low-cost, high-energy-density lithium-ion batteries to reduce costs by reducing the use of inactive components such as separators and current collectors, and extending the driving range of EVs.

[0003] Since the volumetric energy density of lithium-ion batteries depends on the energy per unit volume of active and inactive materials, an increase in volumetric energy density can be achieved by using active materials with high specific capacity and / or thick and high-density electrodes.

[0004] ① Thick electrode / membrane: High loading leads to an increase in specific surface area, but solvent volatilization during the traditional wet drying process leads to severe binder migration behavior. First, the greater the coating thickness, the more difficult it is for the existing binder system to ensure that the electrode has sufficient toughness, and the electrode is more likely to crack during the drying process; second, due to the increase in solvent volatilization time, the probability of uneven spatial distribution of the components in the electrode also increases, which has a negative impact on battery performance. The migration of the binder hinders the transmission of the electrolyte in the electrode, thereby deteriorating the electrode resistance and the corresponding electrochemical performance of high-energy-density lithium-ion batteries. In addition, the binder content near the interface between the electrode film and the current collector is relatively small, and the binder migration behavior leads to a decrease in the adhesion strength between the electrode film and the current collector. Therefore, it is expected to form a thick electrode / membrane (e.g., a thick positive electrode / cathode or negative electrode / anode) that can be adapted and processed in the existing manufacturing process, for use in electrochemical cells or batteries, providing higher energy density to increase storage capacity and / or reduce the size of the battery pack, while maintaining a cycle life similar to other lithium-ion battery packs.

[0005] ② Dry-process electrodes: Traditional lithium-ion battery electrode sheets adopt a wet coating process, which is to fully mix the active material, conductive carbon and binder, evenly dissolve them in an organic solvent, and then coat the fully stirred slurry on the metal current collector. After drying and roller thinning, the electrode sheet of suitable thickness is obtained. However, the wet coating process has certain disadvantages. A large amount of organic solvent N-methylpyrrolidone (NMP) is required in the slurry preparation process. During the drying process, not only the cost of electrode production is increased, but also excessive evaporation of NMP will cause environmental pollution. The dry process of electrode sheets aims to solve the above problems. Dry electrodes are currently divided into two categories: binder fibrillation method and electrostatic spraying. Among them, binder fibrillation is the mainstream. The binder fibrillation method is to mix the active material powder with the conductive agent, add the binder, and then apply an external high shear force to the dry mixture to make the binder fibrillate and bond the electrode film powder. Finally, the mixture is extruded to form a self-supporting film; the electrostatic spraying method is to use high-pressure gas to premix active materials, conductive agents and adhesive particles, and under the action of an electrostatic spray gun, the powder is negatively charged and sprayed onto a metal foil current collector with a positive charge, and then the current collector carrying the adhesive is hot-pressed. After the adhesive melts, it will adhere to other powders and be extruded into a self-supporting film; however, the electrostatic spraying method is not as good as the adhesive fibrillation method in subsequent processability, adhesion stability, electrode flexibility and durability. Therefore, it is a technical problem that needs to be urgently solved in this field to use the adhesive fibrillation method to realize the production of multi-layer / thick electrodes / diaphragms. Summary of the invention

[0006] In view of the above-mentioned deficiencies in the prior art, the present application provides a method for preparing a dry thick electrode sheet which promotes the effective transmission of lithium ions and electrons in an electrode and prepares a thick and dense electrode with uniform binder distribution.

[0007] In order to solve the above technical problems, the technical solution adopted in this application is: a method for preparing a thick electrode by a dry process, the method specifically comprising:

[0008] (1) Powder premixing: Under the condition of controlling the temperature ≤ 18° C., active material powder, binder and conductive agent are mixed in the following proportions: active material: 30-99.5 parts by weight, binder: 0.5-60 parts by weight, conductive agent: 0-30 parts by weight, and stirred to obtain a premix;

[0009] (2) powder fiberization: subjecting the premix obtained in step (1) to rapid shearing and heating to ≤180°C, and obtaining a fiberized powder after reaching a specified temperature;

[0010] (3) Film formation and thinning: The powder obtained after fiberization in step (2) is subjected to a continuous film formation by hot pressing with a pair of rollers, and the film after film formation is continuously passed through a pair of rollers, hot pressed and thinned, and then rolled up to obtain a dry electrode film;

[0011] (4) Laminating the electrode membrane and the current collector: The dry electrode membrane obtained in step (3) is laminated to the current collector on both sides by hot pressing with rollers, and then rolled up to obtain a dry electrode thick electrode roll.

[0012] Furthermore, the active material powder includes but is not limited to positive electrode active materials: single components such as lithium iron phosphate, lithium nickel cobalt manganese oxide, lithium cobalt oxide or their mixtures; or negative electrode materials: single components such as graphite, silicon carbon, nano silicon or their mixtures.

[0013] Furthermore, the binder includes but is not limited to PTFE (polytetrafluoroethylene), PVDF (polyvinylidene fluoride), CMC (sodium carboxymethyl cellulose) and other single components or their mixtures.

[0014] Furthermore, the conductive agent includes but is not limited to single components such as carbon black, carbon nanotubes, graphene, conductive graphite, or mixtures thereof.

[0015] Furthermore, the active material is 30-96 parts by weight, the binder is 2-60 parts by weight, and the conductive agent is 2-20 parts by weight.

[0016] Furthermore, the active material: 96 parts by weight, the binder: 2 parts by weight, the conductive agent: 2 parts by weight; or the active material: 30 parts by weight, the binder: 60 parts by weight, the conductive agent: 10 parts by weight; or the active material: 60 parts by weight, the binder: 20 parts by weight, the conductive agent: 20 parts by weight.

[0017] Furthermore, the shearing equipment used in step (2) can be a double planetary mixer, a screw pump, or a jet mill, and the shearing linear speed is 10-60 m / s.

[0018] Furthermore, the specific process parameters of the one-time hot-pressing continuous film formation by rollers described in step (3) are as follows: the temperature of the rollers is controlled at ≤180°C, the pressure of the rollers is controlled at 0.5-50T, the film forming speed is controlled at 0.1-60m / min, the differential speed ratio of the rollers is controlled at 1:0.5-1:6, and the gap between the rollers is controlled at ≤5000μm.

[0019] Furthermore, the specific process parameters of the hot pressing thinning described in step (3) are as follows: the temperature of the pair of rollers is controlled at ≤180°C, the pressure of the pair of rollers is controlled at 0.5-100T, the thinning speed is controlled at 0.1-100m / min, the differential speed ratio of the pair of rollers is controlled at 1:0.5-1:6, and the gap between the pair of rollers is controlled at ≤5000μm.

[0020] Furthermore, the thickness of the membrane described in step (3) is ≤5100 μm.

[0021] Furthermore, the double-sided lamination in step (4) is as follows: two dry electrode films are sandwiched on a current collector, the thickness of the current collector is in the range of 5-30 μm, and the thickness of the electrode roll finally obtained is ≤5100 μm.

[0022] Furthermore, the temperature of the rollers used in the double-sided lamination in step (4) is controlled at ≤200°C, the pressure of the rollers is controlled at 0.5-200T, the lamination speed is controlled at 0.1-60m / min, and the gap between the rollers is controlled at ≤5000μm.

[0023] Furthermore, the current collector in step (4) is a foil material that performs a conductive function on the battery cell electrode, and generally includes the following categories: copper foil, aluminum foil, carbon-coated copper foil, carbon-coated aluminum foil, composite current collector, composite coating current collector, etc.

[0024] Advantages and beneficial effects of this application:

[0025] 1. The present application utilizes a dry electrode process to refine the hierarchical microstructure of a thick electrode sheet, and achieves a dry electrode with a uniform microstructure suitable for industrial-scale production through the dry electrode process: ① Make the binder and conductive agent more evenly distributed; ② Control the pore size / distribution and conductive network of the electrode to enhance the transmission of lithium ions and electrons in the electrode; ③ Control the calendering process to improve the structural integrity of the active material particles, so that they are free of breakage and the pore distribution in the electrode is uniform.

[0026] 2. The present application realizes a dry electrode with a uniform microstructure suitable for industrial-scale production through a dry electrode process. Specifically, first, the fiberization degree of the binder is improved through the relationship between the fiberization mechanism of the binder and the temperature, so that the binder and the conductive agent are evenly distributed; secondly, the pore size / distribution and conductive network of the electrode are controlled by introducing a multidimensional conductive agent composed of carbon black and graphene, thereby enhancing the transmission of lithium ions and electrons in the electrode; finally, by controlling the calendering process, the structural integrity of the active material particles is improved to prevent them from breaking, and the pore distribution in the electrode is evenly distributed.

[0027] 3. The dry electrode technology of the present application includes the following four steps: (1) powder premixing; (2) powder fiberization; (3) film formation and thinning; (4) electrode membrane and current collector lamination; (5) thick electrode sheet production; This method solves some problems of traditional wet processing: Compared with traditional wet process, dry electrode processing eliminates the solvent drying step, shortens the production cycle, and reduces production cost. The powder premixing process makes the binder and conductive agent more evenly distributed; in addition, by eliminating toxic solvents, dry electrode processing provides environmental benefits; dry electrode processing can prepare thick and dense electrodes with uniform binder distribution, thereby promoting the efficient transmission of lithium ions and electrons in the electrode and improving the electrochemical performance of lithium-ion batteries; the powder premixing and fiberization process controls the pore size / distribution and conductivity of the electrode by controlling the formula and temperature. network, enhancing the transmission of lithium ions and electrons in the electrode; the film forming, thinning and coating processes improve the structural integrity of the active material particles by controlling calendering (including process parameters such as temperature, pressure, speed, differential speed ratio, roll gap, etc.), so that there is no breakage and the pore distribution in the electrode is uniform; the thick electrode / membrane manufacturing process of the present application controls the process parameters of the thick electrode / membrane including formula, temperature, pressure, speed, differential speed ratio, roll gap, etc., and compared with other dry electrodes, the amount of active material in the battery cell of the same capacity is the same, but the thick electrode has fewer battery cell layers, less current collector, lighter battery cell weight, and therefore higher energy density, so it can provide higher energy density to increase storage capacity and / or reduce the size of the battery pack, thereby achieving an increase in volume energy density and further improving the capacity and energy density of the battery cell.

[0028] 4. In the step (1) of the present application, the temperature is controlled at ≤20°C during the powder premixing. This is because the binder will undergo a transformation after the temperature exceeds 18-20°C and is more easily fiberized. Controlling the temperature avoids premature fiberization of the binder. In the step (2) of the present application, after reaching the specified temperature, the specified temperature is an important indicator for controlling the fiberization of the binder. The temperature is not necessarily 180°C. It is actually adjusted according to actual needs and material ratios. This temperature is the natural temperature rise when the material is rapidly sheared. When the temperature naturally rises to a specific temperature, the process ends. Therefore, there is no specific time limit for this process. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 Schematic diagram of the mixture before (a) and after (b) fiberization.

[0030] Figure 2 Schematic diagram of film-forming and thinning process, a. Fiberized material; b. Film-forming; c. Thinning; d. Dry film roll.

[0031] Figure 3Schematic diagram of the electrode lamination process, a. Dry film roll; b. Coated current collector / diaphragm / electrolyte roll; c. Membrane lamination; d. Dry electrode film roll.

[0032] Figure 4 (a) Schematic diagram of traditional wet electrode sheet / (b) dry thick electrode sheet.

[0033] Figure 5 Capacity / cycle performance of dry thick electrode cells.

[0034] Figure 6 Capacity / cycle performance of traditional wet-process battery cells. DETAILED DESCRIPTION

[0035] The following will be combined with the embodiments and drawings to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only preferred embodiments, not all embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0036] The pressure in this application is measured in units of T (t), which is a form of pressure expression commonly used in the industry. Those skilled in the art are aware of the parameters corresponding to the specific pressure adjustment using T as the unit of measurement. The roller press used can adjust the corresponding pressure according to the set value (such as 1 Newton is approximately the pressure generated by a weight of 0.1 kg, or equivalent to a pressure of 1 Pa, 1 Pascal = 1 Newton / square meter (1N / ㎡)).

[0037] Example 1

[0038] The present embodiment provides a method for preparing a dry thick electrode sheet. Based on a specific implementation method, the preparation method of the dry thick film (dry graphite) is as follows: graphite is used as the negative electrode active material, a binder (mass ratio, PTFE:CMC=90:10) and a conductive agent (mass ratio, conductive graphite: carbon nanotube dry powder: graphene dry powder=70:20:10), the mass ratios of active material: binder: conductive agent are 96:3:1 respectively, the negative electrode active material and the conductive agent are added to a mixer, stirred at 4000rpm for 8 minutes, mixed evenly, slowly stirred at 200rpm to cool to 18°C, and then the binder is added, the temperature is controlled to be less than 18°C, stirred at 1000rpm for 10min, mixed evenly, and then the cooling system is turned off, and the fiberization process is completed when the temperature rises to 70°C by natural shearing at 4000rpm. The mixed powder was placed in a one-time film forming / thinning roller press, with a film forming roller gap of 300 μm, a thinning roller gap of 270 μm, a film forming differential speed of 1:2, a thinning differential speed of 1:1, a film forming pressure of 5 T, a thinning pressure of 10 T, and a one-time hot roller pressing / thinning into a self-supporting mold at 110°C to obtain a dry negative electrode membrane with a thickness of about 300 μm; the specific process can be referred to the attached Figure 2 As shown;

[0039] The above-mentioned dry-process negative electrode film and the coating current collector (coated copper foil) were hot-rolled at 110°C for compounding. The coating current collector included a copper foil and a conductive layer arranged on both sides of the copper foil. The single-side thickness of the conductive layer was 1 μm. The hot-rolling gap was 560 μm, and the rolling pressure was 20 T. A dry-process negative electrode sheet with a thickness of about 600 μm was obtained. The dry-process negative electrode sheet was cut into pieces. The specific process can be referred to the attached Figure 3 shown.

[0040] The dry thick electrode sheet obtained in this embodiment is a graphite negative electrode sheet, and the thickness of the electrode sheet reaches 600 μm (see the attached Figure 1 As shown in (b) of Figure 1 (a) is a traditional wet electrode sheet with a thickness of about 300 μm. The single-sided active material density can reach 140 mg / cm 2 .

[0041] As attached Figure 5 As shown in the figure, the black line is the capacity-cycle number relationship diagram of the soft-pack battery cell, which is the capacity of the soft-pack battery cell made of the graphite dry-process negative electrode sheet of Example 1 (about 16Ah); the red line is the capacity retention rate-cycle number relationship, which is the capacity retention rate of the soft-pack battery cell made of the graphite dry-process negative electrode sheet of Example 1 (capacity retention rate > 90% after 300 charge and discharge cycles).

[0042] As attached Figure 6As shown in the figure, the black line is the capacity-cycle number relationship diagram of the soft-pack battery cell, which is the capacity of the soft-pack battery cell made of the graphite negative electrode sheet by the ordinary wet process (about 9Ah); the red line is the capacity retention rate-cycle number relationship, which is the capacity retention rate of the soft-pack battery cell made of the graphite dry negative electrode sheet of Example 1 (the capacity retention rate is >90% after 300 charge and discharge cycles).

[0043] Above Figure 5-6 The number of electrode layers of the two battery cells (wet process / dry process) is designed to be the same.

[0044] Example 2

[0045] The present embodiment provides a method for preparing a dry thick electrode sheet. Based on a specific implementation method, the preparation method of the dry thick film (dry lithium iron phosphate) is as follows: lithium iron phosphate is used as the positive electrode active material, a binder (PTFE: PVDF = 80:20) and a conductive agent (conductive graphite: carbon nanotube dry powder: graphene dry powder = 60:30:10), and the mass ratio of active material: binder: conductive agent is 30:60:10 respectively. The positive electrode active material and the conductive agent are added to a mixer, stirred at 4000 rpm for 5 minutes to mix evenly, slowly stirred at 200 rpm to cool to 18°C, and then the binder is added, the temperature is controlled to be less than 18°C, stirred at 1500 rpm for 6 minutes to mix evenly, and then the cooling system is turned off. The fiberization process is completed when the temperature rises to 180°C by natural shearing at 4000 rpm. The mixed powder was placed into a single film forming / thinning roller press with a film forming roller gap of 2500μm, a thinning roller gap of 2450μm, a film forming differential speed of 1:3, a thinning differential speed of 1:1, a film forming pressure of 50T, a thinning pressure of 100T, and a single hot roller pressing / thinning at 180°C into a self-supporting mold to obtain a dry positive electrode mold with a thickness of about 2500μm.

[0046] The above-mentioned dry-process positive electrode film and the coated current collector (coated aluminum foil) are composited by hot rolling at 200°C. The coated current collector includes an aluminum foil and a conductive layer arranged on both sides of the aluminum foil. The single-sided thickness of the conductive layer is 1 μm, the hot rolling gap is 4900 μm, and the rolling pressure is 200T. A dry-process positive electrode sheet with a thickness of about 5000 μm is obtained, and the dry-process positive electrode sheet is cut into pieces.

[0047] The dry thick electrode obtained in this embodiment is a lithium iron phosphate positive electrode, the thickness of the electrode reaches 5000 μm, and the single-sided surface density of lithium iron phosphate is about 195 mg / cm 2 The high binder content improves the self-supporting mechanical properties of the dry-process positive electrode sheet of small-particle positive electrode material (lithium iron phosphate), and solves the problem that the small particle size of lithium iron phosphate makes it difficult to make a dry self-supporting film.

[0048] Example 3

[0049] The present embodiment provides a method for preparing a dry thick electrode sheet. Based on a specific implementation method, the preparation method of the dry thick film (dry lithium iron phosphate) is as follows: lithium iron phosphate is used as the positive electrode active material, a binder (PTFE:PVDF=90:10) and a conductive agent (conductive graphite: carbon nanotube dry powder: graphene dry powder=50:30:20), and the mass ratio of active material: binder: conductive agent is 30:50:20 respectively. The positive electrode active material and the conductive agent are added to a mixer, stirred at 4000rpm for 8 minutes to mix evenly, and slowly stirred at 200rpm to cool to 18°C, and then the binder is added, the temperature is controlled to be less than 18°C, and stirred at 1500rpm for 10min to mix evenly, and then the cooling system is turned off, and the fiberization process is completed when the temperature is naturally sheared and heated to 160°C at 4000rpm. The mixed powder was placed into a single film forming / thinning roller press with a film forming roller gap of 2500μm, a thinning roller gap of 2450μm, a film forming differential speed of 1:2, a thinning differential speed of 1:1, a film forming pressure of 50T, a thinning pressure of 100T, and a single hot roller pressing / thinning at 180°C into a self-supporting mold to obtain a dry positive electrode mold with a thickness of about 2500μm.

[0050] The above-mentioned dry-process positive electrode film and the coated current collector (coated aluminum foil) are composited by hot rolling at 200°C. The coated current collector includes an aluminum foil and a conductive layer arranged on both sides of the aluminum foil. The single-sided thickness of the conductive layer is 1 μm, the hot rolling gap is 4900 μm, and the rolling pressure is 200T. A dry-process positive electrode sheet with a thickness of about 5000 μm is obtained, and the dry-process positive electrode sheet is cut into pieces.

[0051] The dry thick electrode obtained in this embodiment is a lithium iron phosphate positive electrode, the thickness of the electrode reaches 5000 μm, and the single-sided surface density of lithium iron phosphate is about 195 mg / cm 2 , the high conductive agent content enriches the conductive network and improves the conductive properties of the lithium iron phosphate thick electrode.

[0052] Example 4

[0053] The present embodiment provides a method for preparing a dry thick electrode sheet. Based on a specific implementation method, the preparation method of the dry thick film (dry graphite) is as follows: flake graphite (the flake graphite in this example has conductive properties itself, and no conductive agent needs to be added) is used as the negative electrode active material and the binder (PTFE), and the mass ratio of active material: binder is 99.5:0.5. The negative electrode active material and the binder are added to a mixer, the temperature is controlled to be less than 18°C, and stirred at 1500rpm for 10 minutes to mix evenly, and then the cooling system is turned off, and the fiberization process is completed when the temperature rises to 80°C by natural shear at 4000rpm. The mixed powder was placed into a one-time film-forming / thinning roller press with a film-forming roller gap of 500 μm, a thinning roller gap of 460 μm, a film-forming differential speed of 1:2, a thinning differential speed of 1:1, a film-forming pressure of 20 T, a thinning pressure of 50 T, and a one-time hot roller pressing / thinning into a self-supporting mold at 110°C to obtain a dry-process negative electrode mold with a thickness of about 500 μm.

[0054] The above-mentioned dry-process negative electrode film and the coated current collector (coated copper foil) were composited by hot rolling at 110°C. The coated current collector included a copper foil and a conductive layer arranged on both sides of the copper foil. The single-side thickness of the conductive layer was 0.5 μm. The hot rolling gap was 960 μm, and the rolling pressure was 80 T. A dry-process negative electrode sheet with a thickness of about 1000 μm was obtained, and the dry-process negative electrode sheet was cut into pieces.

[0055] The dry thick electrode sheet obtained in this embodiment is a graphite negative electrode sheet, the thickness of the electrode sheet reaches 1000 μm, and the single-sided surface density of graphite is about 40 mg / cm 2 , combined with flake graphite, increases the surface loading of thick electrodes.

[0056] Example 5

[0057] This embodiment provides a method for preparing a dry thick electrode. Based on a specific implementation method, the preparation method of a dry thick film (dry silicon carbon) is: using silicon carbon (w Si%=40%) is the negative electrode active material, binder (PTFE:CMC=90:10) and conductive agent (conductive graphite: carbon nanotube dry powder: graphene dry powder=50:30:20), the mass ratio of active material: binder: conductive agent is 60:35:5 respectively, the negative electrode active material and conductive agent are added into the mixer, stirred at 4000rpm for 6 minutes, mixed evenly, slowly stirred at 200rpm to cool to 18℃, then the binder is added, the temperature is controlled to be less than 18℃, stirred at 1200rpm for 10min, mixed evenly, then the cooling system is turned off, and the fiberization process is completed when the temperature rises to 90℃ by natural shearing at 4000rpm. The mixed powder was placed into a one-time film-forming / thinning roller press with a film-forming roller gap of 300 μm, a thinning roller gap of 260 μm, a film-forming differential speed of 1:2, a thinning differential speed of 1:1, a film-forming pressure of 20 T, a thinning pressure of 50 T, and a one-time hot roller pressing / thinning into a self-supporting mold at 130°C to obtain a dry-process negative electrode mold with a thickness of about 300 μm.

[0058] The above-mentioned dry-process negative electrode film and the coated current collector (coated copper foil) were composited by hot rolling at 130°C. The coated current collector included a copper foil and a conductive layer arranged on both sides of the copper foil. The single-side thickness of the conductive layer was 1 μm. The hot rolling gap was 580 μm, and the rolling pressure was 80 T. A dry-process negative electrode sheet with a thickness of about 600 μm was obtained, and the dry-process negative electrode sheet was cut into pieces.

[0059] The dry thick electrode obtained in this embodiment is a silicon carbon negative electrode, the thickness of the electrode reaches 600 μm, and its single-sided surface density is about 78 mg / cm 2 The high binder content improves the self-supporting mechanical properties of the dry-process negative electrode sheet of small-particle materials (silicon carbon), solving the problem of difficulty in making dry-process self-supporting films due to small particle size.

[0060] Example 6

[0061] The present embodiment provides a method for preparing a dry thick electrode sheet. Based on a specific implementation method, the preparation method of the dry thick film (dry nano-silicon) is as follows: nano-silicon is used as the negative electrode active material, a binder (PTFE) and a conductive agent (conductive graphite: carbon nanotube dry powder: graphene dry powder = 60:30:10), the mass ratio of active material: binder: conductive agent is 40:50:10 respectively, the negative electrode active material and the conductive agent are added to a mixer, stirred at 4000 rpm for 5 minutes, mixed evenly, slowly stirred at 200 rpm to cool to 18°C, then the binder is added, the temperature is controlled to be less than 18°C, stirred at 1000 rpm for 10 minutes, mixed evenly, then the cooling system is turned off, and the fiberization process is completed when the temperature rises to 65°C by natural shearing at 4000 rpm. The mixed powder was placed into a single film forming / thinning roller press with a film forming roller gap of 300 μm, a thinning roller gap of 280 μm, a film forming differential speed of 1:2, a thinning differential speed of 1:1, a film forming pressure of 5 T, a thinning pressure of 10 T, and a single hot roller pressing / thinning at 110°C into a self-supporting mold to obtain a dry negative electrode mold with a thickness of about 300 μm.

[0062] The above-mentioned dry-process negative electrode film and the coated current collector (coated copper foil) were composited by hot rolling at 110°C. The coated current collector included a copper foil and a conductive layer arranged on both sides of the copper foil. The single-side thickness of the conductive layer was 1 μm. The hot rolling gap was 580 μm, and the rolling pressure was 20 T. A dry-process negative electrode sheet with a thickness of about 600 μm was obtained, and the dry-process negative electrode sheet was cut into pieces.

[0063] The dry thick electrode obtained in this embodiment is a nano-silicon negative electrode, the thickness of the electrode reaches 600 μm, and its single-sided surface density is about 96 mg / cm 2 The high binder content improves the self-supporting mechanical properties of the dry-process negative electrode sheet of small-particle materials (nano-silicon), solving the problem of difficulty in making dry-process self-supporting films due to small particle size.

[0064] Example 7

[0065] The present embodiment provides a method for preparing a dry thick electrode sheet. Based on a specific implementation method, the preparation method of the dry thick film (dry ternary) is: using ternary as the positive electrode active material, binder (PTFE:PVDF=80:20) and conductive agent (conductive graphite: carbon nanotube dry powder: graphene dry powder=70:20:10), the mass ratio of active material: binder: conductive agent is 90:8:2 respectively, the active material and the conductive agent are added to the mixer, stirred at 4000rpm for 6 minutes, mixed evenly, slowly stirred at 200rpm to cool to 18°C, and then the binder is added, the temperature is controlled to <18°C, stirred at 1200rpm for 10min, mixed evenly, and then the cooling system is turned off. The fiberization process is completed when the temperature rises to 85°C by natural shear at 4000rpm. The mixed powder was placed into a single film forming / thinning roller press with a film forming roller gap of 270 μm, a thinning roller gap of 240 μm, a film forming differential speed of 1:3, a thinning differential speed of 1:1, a film forming pressure of 10 T, a thinning pressure of 20 T, and a single hot roller pressing / thinning process at 130°C to form a self-supporting mold to obtain a dry positive electrode mold with a thickness of about 270 μm.

[0066] The above-mentioned dry-process positive electrode film and the coated current collector (coated aluminum foil) were composited by hot rolling at 130°C. The coated current collector included an aluminum foil and a conductive layer arranged on both sides of the aluminum foil. The single-side thickness of the conductive layer was 1 μm. The hot rolling gap was 500 μm, and the rolling pressure was 50T. A dry-process positive electrode sheet with a thickness of about 540 μm was obtained, and the dry-process positive electrode sheet was cut into pieces.

[0067] The dry thick electrode sheet obtained in this embodiment is a ternary positive electrode sheet, the thickness of the electrode sheet reaches 540 μm, and the single-sided active material surface density reaches 200 mg / cm 2 .

[0068] Example 8

[0069] The present embodiment provides a method for preparing a dry thick electrode sheet. Based on a specific implementation method, the preparation method of the dry thick film (dry lithium-rich manganese-based) is: using a lithium-rich manganese-based as a positive electrode active material, a binder (PTFE:PVDF=90:10) and a conductive agent (conductive graphite: carbon nanotube dry powder: graphene dry powder=80:10:10), the mass ratio of active material: binder: conductive agent is 93:5:2 respectively, the active material and the conductive agent are added to a mixer, stirred at 4000rpm for 8 minutes, mixed evenly, slowly stirred at 200rpm to cool to 18°C, and then the binder is added, the temperature is controlled to <18°C, stirred at 1200rpm for 10min, mixed evenly, and then the cooling system is turned off, and the fiberization process is completed when the temperature rises to 90°C by natural shearing at 4000rpm. The mixed powder was placed into a one-time film-forming / thinning roller press with a film-forming roller gap of 400 μm, a thinning roller gap of 360 μm, a film-forming differential speed of 1:3, a thinning differential speed of 1:1, a film-forming pressure of 10 T, a thinning pressure of 20 T, and a one-time hot roller pressing / thinning into a self-supporting mold at 130°C to obtain a dry-process positive electrode mold with a thickness of about 400 μm.

[0070] The above-mentioned dry-process positive electrode film and the coated current collector (coated aluminum foil) were composited by hot rolling at 130°C. The coated current collector included an aluminum foil and a conductive layer arranged on both sides of the aluminum foil. The single-sided thickness of the conductive layer was 1 μm. The hot rolling gap was 760 μm, and the rolling pressure was 50 T. A dry-process positive electrode sheet with a thickness of about 800 μm was obtained, and the dry-process positive electrode sheet was cut into pieces.

[0071] The dry thick electrode sheet obtained in this embodiment is a lithium-rich manganese-based positive electrode sheet with a thickness of 800 μm and a single-sided active material surface density of 200 mg / cm 2 .

[0072] It can be seen from the above embodiments that the thickness of the conventional wet electrode sheet is generally difficult to exceed 400 μm, while the present application can achieve a thickness of more than 600 μm by using a specific dry process. Figure 4 Shown are structural schematic diagrams of the electrode sheet thickness corresponding to the two processes respectively; the electrode sheet prepared by the process of the present application can even reach 5000μm (such as Example 2). Therefore, the process method of the present application can easily increase the surface load of the electrode sheet and solve the application problems in some special fields (high power, high specific energy).

Claims

1. A method for preparing a dry thick electrode, characterized in that: The method specifically includes: (1) Powder premixing: Under the condition of controlling the temperature ≤ 18° C., active material powder, binder and conductive agent are mixed in the following proportions: active material: 30-99.5 parts by weight, binder: 0.5-60 parts by weight, conductive agent: 0-30 parts by weight, and stirred to obtain a premix; (2) Powder fiberization: The premix obtained in step (1) is subjected to rapid shearing and heating to ≤180° C., and after reaching a specified temperature, a fiberized powder is obtained; (3) Film formation and thinning: The powder obtained after fiberization in step (2) is subjected to a continuous film formation by hot pressing with a pair of rollers, and the film after film formation is continuously passed through a pair of rollers, hot-pressed and thinned, and then rolled up to obtain a dry electrode film; (4) Laminating the electrode membrane and the current collector: The dry electrode membrane obtained in step (3) is laminated to the current collector on both sides by hot pressing with rollers, and then rolled up to obtain a dry electrode thick electrode roll.

2. The method for preparing a dry thick electrode according to claim 1, characterized in that: The active material powder includes but is not limited to positive electrode active materials: lithium iron phosphate, lithium nickel cobalt manganese oxide single component or a mixture thereof; or negative electrode materials: graphite, silicon carbon, nano silicon single component or a mixture thereof.

3. The method for preparing a dry thick electrode according to claim 1, characterized in that: The binder includes but is not limited to PTFE, PVDF, CMC single component or a mixture thereof.

4. The method for preparing a dry thick electrode according to claim 1, characterized in that: The conductive agent includes but is not limited to carbon black, carbon nanotubes, graphene, conductive graphite single component or a mixture thereof.

5. The method for preparing a dry thick electrode according to claim 1, characterized in that: The active material is 30-96 parts by weight, the binder is 2-60 parts by weight, and the conductive agent is 2-20 parts by weight.

6. The method for preparing a dry thick electrode according to claim 1, characterized in that: The shearing equipment used in step (2) is a double planetary mixer or a screw pump or a jet mill, and the shearing linear speed is 10-60m / s.

7. The method for preparing a dry thick electrode according to claim 1, characterized in that: The specific process parameters of the one-time hot-pressing continuous film forming by rollers in step (3) are as follows: the temperature of the rollers is controlled at ≤180°C, the pressure of the rollers is controlled at 0.5-50T, the film forming speed is controlled at 0.1-60m / min, the differential speed ratio of the rollers is controlled at 1:0.5-1:6, and the gap between the rollers is controlled at ≤5000μm.

8. The method for preparing a dry thick electrode according to claim 1, characterized in that: The specific process parameters of the hot pressing thinning described in step (3) are: the temperature of the rollers is controlled at ≤180°C, the pressure of the rollers is controlled at 0.5-100T, the thinning speed is controlled at 0.1-100m / min, the differential speed ratio of the rollers is controlled at 1:0.5-1:6, and the gap between the rollers is controlled at ≤5000μm.

9. The method for preparing a dry thick electrode according to claim 1, characterized in that: The thickness of the membrane described in step (3) is ≤5100 μm.

10. The method for preparing a dry thick electrode according to claim 1, characterized in that: The double-sided lamination described in step (4) is as follows: two dry electrode films are sandwiched on a current collector, the thickness of the current collector is in the range of 5-30 μm, and the thickness of the electrode roll finally obtained is ≤5100 μm.

11. The method for preparing a dry thick electrode according to claim 1, characterized in that: The temperature of the rollers used in the double-sided lamination in step (4) is controlled at ≤200°C, the pressure of the rollers is controlled at 0.5-200T, the lamination speed is controlled at 0.1-60m / min, and the gap between the rollers is controlled at ≤5000μm.

12. The method for preparing a thick electrode sheet by dry process according to claim 1, characterized in that: The current collector in step (4) is at least one of copper foil, aluminum foil, carbon-coated copper foil, carbon-coated aluminum foil, composite current collector, and composite coating current collector that serves as a conductive electrode of the battery cell.

Citation Information

Cited By

  • Preparation method for continuously producing lithium thionyl chloride composite carbon electrode

    CN120376580A

  • Negative pole piece, preparation method thereof and lithium ion battery

    CN121439713A